A kinetic study of the reaction between N,N-dimethyl-p-toluidine and its electrogenerated radical cation in a room temperature ionic liquid. - Evans, R; Compton, R (2006)
The reaction between N,N-dimethyl-p-toluidine (DMT) and the radical cation generated through its one-electron oxidation has been studied electrochemically in the room temperature ionic liquid N-methyl-N-butylpyrrolidinium bis(trifluoromethylsulfonyl)imide, [Py14][NTf2]. Kinetic information obtained as linear sweep and cyclic voltammetry collected at 5 microm, 10 microm and 0.3 mm diameter platinum disk electrodes over a range of initial substrate concentrations and scan rates spanning five orders of magnitude was complemented by chronoamperometric measurements designed to probe the rate of diffusion. At the fastest scan rates the homogeneous reactions following the initial electron transfer were effectively out-run, facilitating an assessment of the electrode kinetics using DIGISIM and a validated Nicholson's method. Through digital simulation the voltammetry was then shown to be consistent with a mechanism established for the same reaction in acetonitrile, involving dimerisation of the DMT radicals following an initial and rate-determining proton transfer step. After careful consideration of all parameters, a bimolecular rate constant of (3.4 +/- 1.1) x 10(2) dm3 mol(-1) s(-1) was deduced by fitting the data. This was compared to the equivalent value for acetonitrile and, in light of this, the implications on the viability of ionic liquids for use as alternative mainstream solvents briefly assessed.